The Effect of Oral Stimulation Exercises to Improving the Function of Swallowing, Mastication, and Salivary Flow Rate on the Elderly - Ningtyas, Endah Aryati Eko; Benyamin, Benni; Enhar, Nindita; Ijazati, Kholifah Nur (Indonesian Association Environmental Health of West Kalimantan, 2025)
Oral health issues are prevalent among the elderly due to physiological aging, which often leads to decreased oral muscle function and impairs essential activities such as mastication, swallowing, and salivary secretion. This study aimed to evaluate the effectiveness of oral stimulation exercises in improving these oral functions in elderly individuals. A pre-experimental one-group pre-test and post-test design was conducted involving 28 elderly participants in Pedalangan Village, Semarang, Indonesia. Participants received regular oral stimulation exercises, and assessments were made before and after the intervention. Data were analyzed using the Shapiro-Wilk test for normality, with paired sample t-tests and Wilcoxon tests applied accordingly. The results demonstrated significant improvements in salivary flow rate (p = 0.018), swallowing function (p = 0.000), and mastication ability (p = 0.004). These findings suggest that oral stimulation exercises are an effective non-pharmacological strategy to enhance oral functions among the elderly, potentially improving their overall health and quality of life.